School closures, shelter use, and learning outcomes in the Philippines: Evidence from 2019 TIMSS - Michael Ralph M. Abrigo; Kris A. Francisco; Kevin Carl P. Santos (Asian Development Bank Institute (ADBI), 2024)
In many parts of the world, schools are often used as temporary shelters before, during, and after disasters that may prolong calamity-induced school closures. In this study, we combined student assessment data from the Philippine round of the 2019 Trends in International Mathematics and Science Study with school administrative records and area-level typhoon warnings to assess the impact of short school closures on learning outcomes. Results show that one school closure day induced by school-as-shelter use reduces student achievement by 12% to 14% of a standard deviation, equivalent to roughly half to a full year's worth of learning. This is likely driven by a decline in student interest, rather than by a contraction in the breadth of topics covered in class or by poorer teaching quality. These findings highlight potential hidden disasters from seemingly benign but frequent hazards.
Keywords: H52; I20; Q54; 330; school closure; learning loss; student achievement; TIMSS